MQTT-Based prototype rover with Vision-As-A-Service (VAAS) in an IoT dual-stack scenario - Salazar Chacón, Gustavo David; Venegas, Carlos; Marrone, Luis Armando (2019)
This research and proof-of-concept paper presents the design and implementation of a wireless local and remote-controlled prototype Rover endowed with live video streaming capability (VAAS – Vision-as-a-Service) using MQTT, one of the most effective protocols in IoT environments. This prototype works under an IPv6 WAN connection to Cloud Computing Services and IPv4 WLAN connectivity for local control. Intelligent and Autonomous transportation systems will contribute significantly to develop Smart-Cities, intelligent logistics scenarios, and unmanned search vehicles for places not suitable for human beings, and that is the importance of the present practical paper, as well as to prove the feasibility of using MQTT through dual-stack IoT scenarios.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on eDemocracy & eGovernment (ICEDEG) (6ª : 2019 : Quito, Ecuador)
Keywords: COMPUTACIÓN EN LA NUBE; PYTHON